Attitudes of dental undergraduate students towards patient safety in a UK dental school. (21st January 2019) - Palmer, Julia C.; Blanchard, Jessica R.; Jones, Judith; Bailey, Edmund
Abstract: Objectives: Patient safety is an important issue in health care. In the United Kingdom, wrong site tooth extraction contributes to a significant proportion of adverse or harmful events, coined "never events." Therefore, patient safety within the field of dentistry is of paramount importance. This novel study aims to explore the teaching of patient safety to undergraduate dental students and their current attitudes to the subject. Methods: Focus groups were held at Barts' and The London School of Medicine and Dentistry, QMUL in 2018 to ascertain the views and opinions of thirteen third‐year dental undergraduate students. Results: Thematic analysis was performed on verbatim transcripts. Key themes were highlighted. All students could provide a complete definition of patient safety and of "never events, " with examples. There was a strong emphasis upon awareness of one's own competence and the need for effective communication to maintain patient safety. Small group teaching and the requirement for standardization of teaching were encouraged. The challenge of incorporation of the patient safety concept into the clinical routine without causing repetition during teaching was highlighted. Conclusion: The results show a positive attitude towards the concept and the teaching of patient safety. All students understood patient safety concepts and techniques used to prevent adverse or harmful events. This study proves that teaching on the subject was thought to be of value. It is crucial that the teaching of patient safety is introduced and built upon within the early years of dental undergraduate training so that its practice becomes second nature.